2015
DOI: 10.5057/ijae.14.85
|View full text |Cite|
|
Sign up to set email alerts
|

Automated Color Image Arrangement Method Based on Histogram Matching

Abstract: Abstract:We propose a novel color image arrangement method using an elastic transform based on histogram matching on some kinds of axes. The axes include the lightness axis and Principal Component (PC) axes obtained from Principal Component Analysis (PCA) in the RGB three-dimensional vector space that is an attribute space of color image. In this paper, we mainly present the principle of its automated color arrangement method especially based on Histogram Matching based on Gaussian Distribution (HMGD). Then, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In addition, let y=f(x) be a continuous and monotonic increase function corresponding to cumulative histogram of image brightness level between variables x and y. [7][8][9] And let f(x) be defined by Eq.…”
Section: Histogram Matching Based On Gaussian Distribution (Hmgd)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, let y=f(x) be a continuous and monotonic increase function corresponding to cumulative histogram of image brightness level between variables x and y. [7][8][9] And let f(x) be defined by Eq.…”
Section: Histogram Matching Based On Gaussian Distribution (Hmgd)mentioning
confidence: 99%
“…[4][5] And also, we have illustrated that HMGD processing works to obtain better feeling (or Kansei) impression than that of original image, by the comparative experimental investigation. 6 However, HMGD processing has just worked only for single brightness-peak histogram image. In this paper, we present the improved HMGD for multiple-brightness peak histogram image that we call "HMGD-MBP", using curvature computation and variance estimation.…”
Section: Introductionmentioning
confidence: 99%
“…The example analysis results showed that the scheme could obtain a satisfactory color scheme. Kawakami et al [6] studied the automatic color arrangement method based on Gaussian distribution histogram matching. The experimental results showed that the visual perception of the image processed by the color arrangement method significantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…And we have illustrated that the HMGD processing could improve the feeling (or Kansei) impression better than the original image. 6 In order to further develop the HMGD processing method for better automated one, we noticed that the variance estimation of Gaussian distribution around the neighborhood of peak in the original image's histogram should be performed. Then previously, we presented a variance (or Gaussian width) estimation method using the symmetry of Gaussian function.…”
Section: Introductionmentioning
confidence: 99%